Effects of In Utero Thyroxine Exposure on Murine Cranial Suture Growth. - R Nicole Howie; Emily L Durham; Laurel Black; Grace Bennfors; Trish E Parsons; Mohammed E Elsalanty; Jack C Yu; Seth M Weinberg; James J Cray (PLoS ONE, 2016)
Large scale surveillance studies, case studies, as well as cohort studies have identified the influence of thyroid hormones on calvarial growth and development. Surveillance data suggests maternal thyroid disorders (hyperthyroidism, hypothyroidism with pharmacological replacement, and Maternal Graves Disease) are linked to as much as a 2.5 fold increased risk for craniosynostosis. Craniosynostosis is the premature fusion of one or more calvarial growth sites (sutures) prior to the completion of brain expansion. Thyroid hormones maintain proper bone mineral densities by interacting with growth hormone and aiding in the regulation of insulin like growth factors (IGFs). Disruption of this hormonal control of bone physiology may lead to altered bone dynamics thereby increasing the risk for craniosynostosis. In order to elucidate the effect of exogenous thyroxine exposure on cranial suture growth and morphology, wild type C57BL6 mouse litters were exposed to thyroxine in utero (control = no treatment; low ~167 ng per day; high ~667 ng per day). Thyroxine exposed mice demonstrated craniofacial dysmorphology (brachycranic). High dose exposed mice showed diminished area of the coronal and widening of the sagittal sutures indicative of premature fusion and compensatory growth. Presence of thyroid receptors was confirmed for the murine cranial suture and markers of proliferation and osteogenesis were increased in sutures from exposed mice. Increased Htra1 and Igf1 gene expression were found in sutures from high dose exposed individuals. Pathways related to the HTRA1/IGF axis, specifically Akt and Wnt, demonstrated evidence of increased activity. Overall our data suggest that maternal exogenous thyroxine exposure can drive calvarial growth alterations and altered suture morphology.